Correction: An Evolution-Based Screen for Genetic Differentiation between Anopheles Sister Taxa Enriches for Detection of Functional Immune Factors. - Christian Mitri; Emmanuel Bischoff; Eizo Takashima; Marni Williams; Karin Eiglmeier; Adrien Pain; Wamdaogo M Guelbeogo; Awa Gneme; Emma Brito-Fravallo; Inge Holm; Catherine Lavazec; N'Fale Sagnon; et al. (PLoS Pathogens)
[This corrects the article DOI: 10.1371/journal.ppat.1005306.].